CONNECTION AMIDST PERSONAL INCOME TAX AND REVENUE GENERATION IN NORTH CENTRAL STATES, NIGERIA - Tajudeen Adejare ADEGBITE; Taiwo Abdulrahim IBRAHIM; Adeniyi Akinade ADELEKE (JRAMB (Jurnal Riset Akuntansi Mercubuana), 2022)
ABSTRACTThe impact of personal income tax on North Central states revenue generation in Nigeria was examined in this work. Data such as PAYE, direct assessment were from gotten from the National Bureau of Statistics, while Agricultural Credit Guarantee Scheme Fund Loan, and Population were sourced from CBN bulletin respectively. Panel Data Analysis, trend analysis and descriptive analysis were used to analyze the data sourced from Kwara, Kogi, Niger, Benue, Plateau, and Nasarawa States. With thorough assessment and analyses, it was concluded that personal income tax has positive significant impact on internally generated revenue in North central states in Nigeria. That is personal income tax contributed significantly to revenue generation of the selected states. Personal income tax has been seen as a pertinent tool in revenue generation of the North central states in Nigeria. Based on the findings of this study, it is recommended that in order to widen the states’ tax revenue through personal income tax, priority should be given to automation of tax remittance to cover all aspect of personal income tax (PAYE and Direct Assessment) in the states in order to enable prompt remittance of personal income tax especially those states with lower IGR so as to boost their internally revenue generation ultimately.